Letters between Alejandro Herrero and Félix Candela: friendship, architecture, and construction techniques - Rodrigues de Oliveira, Silvana (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The architects Alejandro Herrero Ayllón and Félix Candela Outeriño forged a solid friendship as students at the Escuela Superior de Arquitectura de Madrid (graduating class of 1935); they shared different activities and study trips and jointly authored notes on Strength of Materials. Following the vicissitudes of the Spanish Civil War, they managed to avoid the supposedly strict control of the period and continued this friendship through a lengthy correspondence. Following a study methodology which contrasts primary sources, this article delves into these letters, a wealth of autobiographical information. In these documents, which are preserved at the Municipal Archive of Huelva and Library Archive at Columbia University (New York), the authors described their lives, different examples of architecture, construction techniques, early conferences, and articles, offering each other support. Exiled to Mexico, Candela was working on his first structural projects, which earned him international recognition. Meanwhile, Herrero, based in Huelva, was building his first projects for social housing and villages, incorporated into the settings and adjusted to the harsh reality of the Spanish post-war period. He then went on to design major buildings which were included in the Iberian Docomomo. All these documents expose the historical contexts that conditioned their lives and architectures, providing new perspectives.
Keywords: Architecture; structural dialogues; construction techniques, tradition and modernity; epistolary correspondence